Car Parking Monitoring System Based on Location Plate Detection Using Web Camera - Saputra, Eko; Paramytha IS, Nina; Fitriani, Endah; Ariyadi, Tamsir; Hanif Ath Tarech, Affan (PTE FTK UIN Ar-Raniry, 2026)
This research aims to design a car parking monitoring system based on license plate detection using a webcam to improve efficiency and accuracy in parking area management. The scope of the research includes hardware design using an ESP32 microcontroller, ultrasonic sensors, proximity sensors, a 16x2 LCD, servo motors, and a thermal printer. The research methodology involves literature review, as well as laboratory testing and data validation. The system is evaluated based on its ability to accurately detect vehicle license plates, monitor parking space availability in real-time, and automatically record vehicle entry and exit data. Experimental results show that the system correctly detects, matches it with a database, and controls access to the parking area. All components operate within the specified voltage range, with measurement errors remaining below 5%. The system successfully records vehicle entry and exit times, and the website interface updates parking space availability in real-time based on sensor readings. In conclusion, the proposed system is effective in helping operators monitor slot availability, minimize vehicle placement errors, and simplify the parking process with automation